Finding meaning in a historical fiction of cold war: A case study of Pamuntjak’s Question of Red - Kaumpungan, Margihon Bayu Putra (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The Cold War and its legacy in Southeast Asia, has been considered as one of the darkest parts of the region’s history including in Indonesia. Efforts to capture the painful memory of the Cold War had been established through various means including fictional storytelling. Among many literature discussing the dark history of the era, Laksmi Pamuntjak “Question on Red” had its distinctive presence since it was written in English. The utilization of English as a medium opens the door for English speaking readers to be able to dwell into a literature work that is considerably unfamiliar to their cultural context. Utilizing reception studies as a tool, this research is comparing Indonesian and non-Indonesian audiences in actively interpreting, consuming, and responding to historical fiction. The sociocultural background of the reader played a major role in how historical fiction is understood. Yet, when it comes to universal norms, all readers share a similar perspective. The study enriched the understanding of literature, particularly in exploring readers’ responses that come from different cultural contexts.